2006
DOI: 10.1292/jvms.68.1179
|View full text |Cite
|
Sign up to set email alerts
|

A Fusion Protein of IgG Fc and Mouse-Derived Antigen on the Surface of Pseudorabies Virus Particles Does Not Accelerate Production of Harmful Auto-Reactive Antibodies

Abstract: ABSTRACT. Previously we reported that immunization with pseudorabies virus (PRV), harboring chimeric Fc on the surface of the virus particles (PRV/Fc), induced higher immune responses than normal PRV particles. The chimeric Fc was fused with mouse transferrin receptor of transmembrane domain (mTR) and the Fc region of immunoglobulin G1. Since it has been reported that some chimeric protein of Fc and self-antigen induce auto-reactive antibodies, in this present study, we examined whether PRV/Fc induces auto-rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Since CETP is a self-antigen with low immunogenicity, which may lead to a low immune response [15] , we thus designed a novel anti-CETP vaccine (Fc-CETP 6 ) composed of the Fc domain of rabbit IgG fused to a linear repeats epitope within a region responsible for CETP-VLDL/LDL binding. The Fc domain binds to the Fc receptor, facilitating antigen delivery to antigen-presenting cells through receptor-mediated endocytosis [16] , [17] , which is more efficient than phagocytosis, leading to antigen presentation through the MHC II pathway [18] . It has been demonstrated that carrier proteins bearing linear repeats of epitope are highly effective in inducing strong B cell activation [19] .…”
Section: Introductionmentioning
confidence: 99%
“…Since CETP is a self-antigen with low immunogenicity, which may lead to a low immune response [15] , we thus designed a novel anti-CETP vaccine (Fc-CETP 6 ) composed of the Fc domain of rabbit IgG fused to a linear repeats epitope within a region responsible for CETP-VLDL/LDL binding. The Fc domain binds to the Fc receptor, facilitating antigen delivery to antigen-presenting cells through receptor-mediated endocytosis [16] , [17] , which is more efficient than phagocytosis, leading to antigen presentation through the MHC II pathway [18] . It has been demonstrated that carrier proteins bearing linear repeats of epitope are highly effective in inducing strong B cell activation [19] .…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that carrier proteins containing the immunoglobulin (Ig) Fc domain (IFD) facilitate uptake through receptor-mediated endocytosis [13, 1821] and hence antigen presentation through the MHC II pathway in APCs [22–24]. It has also been demonstrated that carrier proteins containing antigen clustering domain (ACD) are highly effective in inducing strong B cell activation [12, 2527].…”
Section: Introductionmentioning
confidence: 99%